2021
DOI: 10.1177/26338076211014594
|View full text |Cite
|
Sign up to set email alerts
|

Examining the overlap of young people’s early contact with the police as a person of interest and victim or witness

Abstract: There is known to be considerable overlap among the victims and perpetrators of crime. However, the extent of this overlap early in life among children and young adolescents is not clear. We examined the sociodemographic profiles of young people who had early contact with police regarding a criminal incident as a person of interest, victim and/or witness, as well as the patterns of multiple police contact types from birth to 13 years of age. Data were drawn from a longitudinal, population-based sample of 91,63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Parental history of criminal offending in this group was high; over three-quarters had a parent with a criminal offending history compared to around one-third in the total sample. Research on young people who are both victims and offenders has similarly found higher levels of vulnerability for some risk factors (Athanassiou et al, 2021;Cuevas et al, 2022;Randone & Thomas, 2022). Specifically, in their study of Latino young people, Cuevas et al (2022) found that while cultural and mental health variables were not different across groups (i.e., delinquent-victims, primarily victims, primarily delinquent, or neither delinquent nor victims), delinquent-victim young people were differentiated by degree of family support and self-reported anger/hostility.…”
Section: Discussionmentioning
confidence: 99%
“…Parental history of criminal offending in this group was high; over three-quarters had a parent with a criminal offending history compared to around one-third in the total sample. Research on young people who are both victims and offenders has similarly found higher levels of vulnerability for some risk factors (Athanassiou et al, 2021;Cuevas et al, 2022;Randone & Thomas, 2022). Specifically, in their study of Latino young people, Cuevas et al (2022) found that while cultural and mental health variables were not different across groups (i.e., delinquent-victims, primarily victims, primarily delinquent, or neither delinquent nor victims), delinquent-victim young people were differentiated by degree of family support and self-reported anger/hostility.…”
Section: Discussionmentioning
confidence: 99%
“…Other explanations may include environmental factors, such as low income that may follow mental illness or justice involvement, or other family circumstances that increase the likelihood of both parental adversity and child victimisation. Beyond the need to prevent children's experiences of indirect and direct victimisation given the inherent harm involved, both these types of victimisation have been shown to be associated with an increased likelihood of offending (Farrell & Zimmerman, 2018 ; Hartinger‐Saunders et al., 2011 ) and re‐victimisation (Athanassiou et al., 2021 ; Ellonen & Salmi, 2011 ), in addition to the link between indirect exposure to violence and risk of direct victimisation (Finkelhor et al., 2015 ; Hamby et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context a person of interest is defined as an individual who has not necessarily been formally accused of a crime but is of interest to the police during the investigation of a criminal incident, such as assault, robbery or fraud, or a non-criminal incident, such as traffic accident, natural disaster and missing person; a victim is a person who suffers harm as a direct result of a criminal or non-criminal incident investigated by police; a witness is a person who sees, hears or experiences a criminal or non-criminal incident investigated by police (Whitten et al, 2020). It was possible for children to have contact with police for more than one reason during the observation period and previous analyses have identified considerable overlap (see Athanassiou et al, 2021). Police contact in relation to 'children at-risk' incidents or mandatory reporting requirements were not included.…”
Section: Offspring Police Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…1.An adolescent is recorded as a person of interest when they come under notice by the NSWPF as the result of their involvement in a police incident. This involvement may or may not result in their arrest or legal action being issued (Athanassiou et al, 2021). All police incidents when recorded on the COPS database are further classified with one or more associated factors.…”
mentioning
confidence: 99%